Urgensi Pengaturan Tindakan Whistleblowing terkait Rahasia Dagang untuk Kepentingan Umum Berdasarkan Perbandingan Undang-Undang Rahasia Dagang dan Directive (EU) 2016/943 - Azka Ridho Syahputra; Rika Ratna Permata; Ranti Fauza Mayana (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
Trade Secrets are a form of Intellectual Property that provide protection for confidential information owned by a legal subject. While Trade Secret protection offers benefits for individuals in running a business, it can also be misused to conceal legal violations. This research aims to identify how Trade Secret regulations in Indonesia provide protection for individuals who disclose Trade Secrets in the public interest, as well as to examine the urgency of such regulation by comparing the provisions of the Indonesian Trade Secret Law with Directive (EU) 2016/943. This study employs a normative juridical method with a comparative approach. The researcher conducts a literature study by comparing the Indonesian Trade Secret Law with Directive (EU) 2016/943 and relevant legal theories. The results show that the current regulation of whistleblowing on Trade Secrets for the public interest in Indonesian positive law remains very limited. There is an urgent need to expand protection for individuals who disclose Trade Secrets in the public interest. Indonesia may use Directive (EU) 2016/943 as a reference to broaden the provisions of its Trade Secret Law, in order to ensure the protection of public interest without disregarding the rights of Trade Secret holders.